The oral-gut microbiota relationship in healthy humans: identifying shared bacteria between environments and age groups - Costa, Carolina F. F. A.; Correia-de-Sá, Teresa; Araujo, Ricardo; Barbosa, Fernando; Burnet, Philip W. J.; Ferreira-Gomes, Joana; Sampaio-Maia, Benedita (Frontiers in Microbiology, 2024)
Introduction Although the oral cavity and the gut are anatomically continuous regions of the gastrointestinal tract, research on the relationship between oral and gut microbiota remains sparse. Oral-gut bacterial translocation is mostly studied in pathological contexts, thus evidence of translocation in healthy conditions is still scarce. Studying the oral-gut microbiota relationship in humans in different life stages is necessary in order to understand how these microbial communities might relate throughout life. Methods In this study, saliva and fecal samples were collected from healthy participants (39 children, 97 adults). Microbiota analysis was carried out by sequencing the V4 region of the 16S ribosomal RNA gene, followed by amplicon sequence variant (ASV) analysis. Results and discussion Although the oral and gut microbiota are vastly different, a subset of 61 ASVs were present in both the oral cavity and gut of the same individual, and represented 1.6% of all ASVs detected. From these, 26 ASVs (classified into 18 genera: Actinomyces, Rothia, Bacteroides, Porphyromonas, Prevotella, Alistipes, Fusobacterium, Neisseria, Haemophilus, Akkermansia, Solobacterium, Granulicatella, Streptococcus, Gemella, Mogibacterium, Dialister, Veillonella, Christensenellaceae R-7 group) were present in both children and adults, suggesting the possibility of persistent colonization of both habitats by these microorganisms, initiating in childhood. Additionally, 62% of shared ASVs were more abundant in the oral cavity, indicating that oral-to-gut translocation may be the main route of translocation between environments, and highlighting that this phenomenon might be more common than previously thought in healthy individuals of all ages.